FORMULATION AND CHARACTERIZATION OF ORGANIC- INORGANIC HYBRID FILM FOR TRANSDERMAL DRUG DELIVERY - Taksande, Jayshree Brijesh; Gupta, Mona; Trivedi, R V; Wadher, K J; Umekar, M J (Journal of Applied Pharmaceutical Research, 2016)
A novel organicÃ¢â¬âinorganic hybrid film-forming gel for transdermal application was developed by poly vinyl alcohol using Di methyl polysiloxane as an inorganic-modifying agent, poly N-vinyl pyrrolidone as a tackifier and PEG 200 as a plasticizer. The hybrid film-forming gel can be directly applied on the skin forms a thin bioadhesive film with transparent and non- greasy feeling. The mechanical and bioadhesive properties of films produced from the hybrid gels were investigated and the results showed that the incorporation of appropriate Di methyl polysiloxane into the PVA matrix significantly improves the mechanical strength and skin adhesion properties of the resulting film.ÃÂ  In conclusion, the bioadhesive films formed from organicÃ¢â¬âinorganic hybrid gel holds excellent qualities for application on the skin and may provide a promising formulation for transdermal delivery of drugs, especially when the patient acceptability from an aesthetic perspective of the dosage form is a main consideration.